Food Technology–Driven Utilization of Seaweed Waste as a Source of Health-Promoting Bioactive Compounds - Yuhendra AP; Reza Kusuma Nurrohman; Mi’raj Fuadi; I Wayan Sweca Yasa; Setyaning Pawestri; Nur Afni; Qabul Dinanta Utama; Wiharyani Werdiningsih; Sukmawaty Sukmawaty; Diah Ajeng Setiawati; Made Gendis Putri Pertiwi; Fuad Sauqi Isnain; Endang Purnama Dewi; Elya Antariksana Bachmida; Wan Rosli Bin Wan Ishak; Haslina Ahmad (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community engagement activity focused on the utilization of native seaweed, particularly Kappaphycus alvarezii, as a source of bioactive compounds with the potential to enhance functional food products developed by small and medium enterprises (SMEs) in Kampung Nelayan Merah Putih, Ekas Buana Village, East Lombok. The activity was conducted on 22 January 2026 and centred on the delivery of the module entitled “Exploring Kappaphycus alvarezii as a Sustainable Source of Bioactive Compounds for Functional Food Innovation.” The session was delivered directly by Prof. Wan Rosli Bin Wan Ishak, accompanied by Prof. Haslina Ahmad and collaborators from the Synthesis and Bioactive Materials research group of USM–UPM. The programme included theoretical presentations on the bioactive composition of K. alvarezii, opportunities for the sustainable utilization of processing by-products, and an introduction to the concept of algae-based functional foods tailored for coastal SMEs. Participants were also invited to visit a local seaweed production facility to gain a deeper understanding of the supply chain, raw material quality, and the potential conversion of processing waste into value-added products. The expected outcomes include enhanced technical and entrepreneurial capacities among SME actors, improved ability to design algae-based functional food products, and the strengthening of an environmentally sustainable local supply chain. The long-term impact will be assessed through improvements in production efficiency, the adoption of basic food safety and quality practices (GMP/SSOP), and the potential increase in income among coastal SME practitioners. Overall, this initiative highlights the value of international–local partnerships in advancing sustainable tropical food innovation.